2023
DOI: 10.1002/adfm.202307157
|View full text |Cite
|
Sign up to set email alerts
|

Confined‐Synthesis of Ceria in Tubular Nanoclays for UV Protection and Anti‐Biofilm Application

Yue Feng,
Di Zhang,
Xiangyu Chen
et al.

Abstract: UV radiation is the main cause of skin aging and cancers. Commercial sunscreens suffer from low efficacy and poor safety, while ceria nanocrystals are promising inorganic UV filters. Herein, the lumen of natural halloysite clay nanotubes (HNTs) is employed for the confined growth of ceria nanocrystals, which can effectively tailor the particle size, morphology, distribution, and oxygen vacancies of the ceria. The ceria in HNTs lumen exhibits increased UV protection and catalytic activity, while the outer surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The micromorphology of the reduced catalysts was examined by TEM characterization (Figure ). It can be seen that most Ni particles are dispersed on the outer surface of HNTs, and a small fraction of Ni particles may enter into the lumen of HNTs (Figure S3) due to the vacuum operation. , The average Ni particle size of Ni(17%)/HNTs- x AC is smaller than that of Ni(17%)/HNTs (Table ), suggesting that HNTs pretreated with HNO 3 can improve the dispersion of metal particles. It is worth noting that the size of Ni nanoparticles grows when the concentration of HNO 3 solution increases from 8 to 10 mol/L.…”
Section: Resultsmentioning
confidence: 98%
“…The micromorphology of the reduced catalysts was examined by TEM characterization (Figure ). It can be seen that most Ni particles are dispersed on the outer surface of HNTs, and a small fraction of Ni particles may enter into the lumen of HNTs (Figure S3) due to the vacuum operation. , The average Ni particle size of Ni(17%)/HNTs- x AC is smaller than that of Ni(17%)/HNTs (Table ), suggesting that HNTs pretreated with HNO 3 can improve the dispersion of metal particles. It is worth noting that the size of Ni nanoparticles grows when the concentration of HNO 3 solution increases from 8 to 10 mol/L.…”
Section: Resultsmentioning
confidence: 98%
“…For example, Tao et al found that the introduction of molybdenum oxide promoted the dispersion of vanadium oxide species on TiO 2 support. , As the literature reported, the ionic radius of Cu 2+ (72.0 pm) was smaller than that of Ce 3+ (101.3 pm). When Cu 2+ and Ce 3+ coexisted in aqueous solution, Cu 2+ ions could more easily penetrate the tube of TiO 2 NTs than Ce 3+ . , To maintain the potential balance of the solution, Ce 3+ ions were mainly focused on the outer surface of the tube. After calcination, most of the CuO x species were inclined to enter the TiO 2 NTs, while most of the CeO x species were mainly anchored on the outer surface .…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely used in various fields, 27,28,31−35 including pollutants removal, catalysis, energy storage, polymer filler, drug delivery, etc., attributing to its hollow tubular structure, high specific surface area, and opposite surface charges. 35−37 Especially, HNT is supposed to be a potential carrier for supporting nanocatalysts [31][32][33]38 and trapping AB into its channels or coating AB on its surface in view of its distinct microstructure and the abundance of Al/Si-OH groups on inner/outer surfaces. 34,39,40 Assembling HNT into hierarchical porous aerogel can further increase the porous volume for supporting and trapping more matrix and inhibiting their aggregation 41−44 because aerogels have more complex porosity, lower density, and higher surface area.…”
Section: Introductionmentioning
confidence: 99%
“…It usually has a tubular shape with an inner diameter of 5–20 nm and a length of 0.5–2 μm. Halloysite nanotubes (HNT) are composed of silyl groups (Si-O-Si) on their outer surfaces and aluminum trihydrate octahedral groups (Al-OH) on their inner surface. It has been widely used in various fields, ,, including pollutants removal, catalysis, energy storage, polymer filler, drug delivery, etc., attributing to its hollow tubular structure, high specific surface area, and opposite surface charges. Especially, HNT is supposed to be a potential carrier for supporting nanocatalysts , and trapping AB into its channels or coating AB on its surface in view of its distinct microstructure and the abundance of Al/Si-OH groups on inner/outer surfaces. ,, Assembling HNT into hierarchical porous aerogel can further increase the porous volume for supporting and trapping more matrix and inhibiting their aggregation because aerogels have more complex porosity, lower density, and higher surface area. For example, Ma et al in our group have encapsulated phase change material lauric acid into HNT aerogel, which can significantly improve the loading capacity of lauric acid …”
Section: Introductionmentioning
confidence: 99%